PENGARUH PEMBERIAN EKSTRAK DAUN SALAM (Syzygium polyanthum Wight.) TERHADAP GLIBENKLAMID DALAM MENURUNKAN KADAR GLUKOSA DARAH MENCIT (Mus musculus) YANG DIINDUKSI ALOKSAN - Nur Hikmah; Yuliet Yuliet; Khildah Khaerati (Universitas Tadulako, 2016)
The use of herbal medicines and synthetic drugs simultaneously carried out by diabetics for the maintenance of blood glucose levels, such as the use of glibenclamide and bay leaf. This research was carried out to know the impact of administration bay leaf extract on glibenclamide in lowering blood glucose levels on mices that induced by alloxan. This research used 40 male mices which were divided into 8 groups. Before the experiment, the mices were first induced by alloxan (70 mg/kg BW) intravenously. The negative control was the group that given Na CMC 0,5%, KG was the control of glibenclamide 0,65 mg/kg BW, group DS1, DS2, DS3 were the control of single bay leaf extract with each dose 250 mg/kg BW, 500 mg/kg BW, and 750 mg/kg BW, group KD1, KD2, KD3 were the combination group of glibenclamide and bay leaf extract with each dose glibenclamide combined bay leaf extract 250 mg/kg BW, glibenclamide combined bay leaf extract 500 mg/kg BW, and glibenclamide combined bay leaf extract 750 mg/kg BW, with an hour interval. The data were statistically analyzed using ANOVA (Analysis of Variance) at 95% confidence interval with parameter of blood glucose levels difference between before and after treatment. The results showed that the administration of bay leaf extract gave significant impact on glibenclamide in lowering blood glucose levels and the effective dose was the combination of glibenclamide 0,65 mg/kg BW and bay leaf extract 250 mg/kg BW